Virtual Burglary: Exploring the Potential of Virtual Reality to Study Burglary in Action. (February 2017) - van Gelder, Jean-Louis; Nee, Claire; Otte, Marco; Demetriou, Andrew; van Sintemaartensdijk, Iris; van Prooijen, Jan-Willem
Objectives: This article explores the potential of virtual reality (VR) to study burglary by measuring user responses on the subjective, physiological, and behavioral levels. Furthermore, it examines the influence of individual dispositions, such as sensation seeking and self-control, on behavior during a virtual burglary event. Methods: Participants, male university undergraduates ( N = 77), could freely move around a virtual neighborhood wearing a VR headset and using a game controller and were instructed to burgle one of the houses in the neighborhood. Participant movement, items stolen from the house, and heart rate (HR) were recorded throughout the burglary event. Individual dispositions were measured before, and subjective user responses were measured after, the event. Additionally, we experimentally varied whether there was an alarm sounding and participants' beliefs about the chance of getting caught (deterrence). Results: Participants reacted subjectively to the burglary event by reporting high levels of presence in the virtual environment (VE) and physiologically by showing increased HRs. In terms of behavior, high deterrence resulted in fewer items being stolen and a shorter burglary. Furthermore, sensation seekers stole more valuable items, while participants high in conscientiousness stole fewer items. Conclusions: The results suggest that VEs have substantial potential for studying criminal behavior.